Robinia pseudoacacia L. Plantation in Erosion Control Areas of Artvin Region, Turkey - Ayan, Sezgin; Yüksek, T.; Ölmez, Zafer (Role of Multipurpose Agriculture in Sustaining Global Environment Agroenviron 2004 – Udine, Italy, 20-24 October 2004,Proceedings, P: 511-514., 2004)
The aim of this study is to determine diameter of root collar growth and height of Robinia pseudoacaia L. seedlings planted in 2000 in erosion control area located in the southeastern of Artvin, Turkey. Three sample plots, each with three replications of 30 seedlings planted in it, were chosen out of the 552 ha erosion control area. At the end of the third growing season, height and root collar diameter of the seedlings were measured. In addition, both aspect and slope locations of the sample plots were also determined. The inclination of sample plots was approximately the same. Effects of the exposure and shape location of slope on growth of the seedlings were investigated. Results show that the exposure and location of slope affected the heights and root collar diameters of the seedlings.
Keywords: Robinia pseudoacacia L., erosion, plantation